Risk factors for hospitalization at the pediatric intensive care unit among infants and children younger than 5 years of age diagnosed with infectious diseases - Judah Freedman; Eugene Leibovitz; Ruslan Sergienko; Amalia Levy (Elsevier, 2023)
Background: Children hospitalized with infectious diseases may develop severe, life-threatening conditions, often requiring admission to pediatric intensive care unit (PICU). The objectives of this study were to identify independent risk factors for PICU hospitalization with an infectious disease in children <5 years of age. Methods: In southern Israel, two populations live side by side: the middle-high income Jewish population and the low-income Bedouin population, both receiving equal and free medical care at the only tertiary medical center in the area. The study population included all children born in southern Israel and hospitalized at PICU with an infectious disease during 1991-2012. Risk factors for PICU hospitalizations were retrospectively studied by Kaplan-Meier and Cox proportional hazard survival analyses. Results: 9951 Jewish children and 18,002 Bedouin children were enrolled; overall, 1135 episodes of PICU hospitalizations with an infectious disease were recorded (879, 77.4% Bedouin and 256, 22.6% Jewish patients). Bedouin children had a higher risk for PICU hospitalization with an infectious disease compared with Jewish children (adjusted Hazard Ratio [adj. HR] 1.7, 95% CI 1.5-2.0); maternal multiparity and low-birth weight (<2500 g) were additional risk factors for PICU hospitalization with an infectious disease compared to firstborns (adj. HR = 1.2, 95% CI 1.0-1.5) or to children with a birth weight ≥2500 g (adj. HR = 1.5, 95% 1.2-1.9). Older age was a protective factor for PICU hospitalization (adj. HR = 0.98, 95% CI 0.97-0.99). Children hospitalized with a central nervous system infection had the highest risk of PICU hospitalization (adj. HR 6.8, 95% CI 5.5-8.4), followed by those with urinary tract infections (UTI, adj. HR 3.1, 95% CI 2.5-3.8) and those with lower respiratory tract infections (LRTI, adj. HR 2.9, 95% CI 2.4-3.4). Conclusion: Bedouin ethnicity, low birth weight, maternal multiparity and younger age were significant risk factors for PICU hospitalizations with an infectious disease. Among the infectious diseases analyzed, CNS infection had the highest risk for PICU hospitalization, followed by UTI and LRTI.